Umbilical Cord Mesenchymal Stem Cells Ameliorate Inflammation-Related Tumorigenesis via Modulating Macrophages - Yanxia Fu; Jun Li; Mengdi Li; Junfeng Xu; Zheng Rong; Fangli Ren; Yinyin Wang; Jianqiu Sheng; Zhijie Chang (Stem Cells International)
Mesenchymal stem cells (MSCs) have been documented to be effective for the therapy of inflammation-related diseases but raised concerns on possible tumorigenic effects. Since most of the tumors are induced or promoted by chronic inflammation, one could expect that MSCs might be beneficial for the cancer therapy because of their potent roles on inhibiting inflammation. This study is aimed at performing a safety evaluation and evaluating the role of human umbilical cord mesenchymal stem cells (HUC-MSCs) on tumorigenesis. We found that HUC-MSCs cultured within 20 generations had no significant changes in proliferation, cell cycle, cellular senescence, apoptosis, and expression of mesenchymal stem cell markers. HUC-MSCs were unable to form any tumor in immunodeficiency or normal mice with or without inflammatory stimulation. Intriguingly, we observed that HUC-MSCs inhibited tumorigenesis in B16-derived or AOM/DSS-induced colon cancer models. We reasoned that the effect of HUC-MSCs on tumorigenesis might be through regulating the inflammatory response. Indeed, HUC-MSCs dramatically ameliorated the disease symptoms and pathological changes of DSS-induced colitis mice. We deciphered the mechanism that HUC-MSCs inhibited tumorigenesis through reducing the proportion of macrophages, which were decreased in the mice suffered from AOM/DSS-induced colon cancer. Correspondingly, the expression levels of TNF-α and IL-6, which were secreted by macrophages, were significantly decreased in the plasma of colon cancer and colitis mice after injection of HUC-MSCs. This study revealed the role of inhibiting macrophages and shed light on the therapeutic application of HUC-MSCs in inflammation-induced tumorigenesis.